Penerapan Model Project-Based Learning dalam Meningkatkan Kemandirian Belajar dan Motivasi Siswa di SDN 036 Tanggabosi - Khairunnisa Khairunnisa; Inda Warni; Ifrah Muliyani E. Pulungan; Rama Nida Siregar (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2026)
This study aimed to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving the learning independence of fourth-grade students at SDN 036 Tanggabosi, an elementary school with limited learning facilities. This research employed a descriptive qualitative approach involving 19 students as research subjects. Data were collected through learning independence tests, observations of project activities, and semi-structured interviews with teachers and students. The findings indicate a significant improvement in students’ self-regulated learning abilities, as reflected in their enhanced capacity to plan, monitor, and evaluate their learning processes independently. Project activities were found to increase intrinsic motivation, social interaction, and students’ sense of responsibility toward their learning. Despite limited school facilities, the fourth-grade students of SDN 036 Tanggabosi demonstrated the ability to utilize simple materials from their surrounding environment to complete the projects, confirming that the effectiveness of PjBL does not rely on the availability of complete facilities but rather on participatory and contextual instructional design.